Evaluation and classification of sorghum (Sorghum bicolor) male sterile lines for fodder traits using multivariate analyses - YADAV, RAJESH; PAHUJA, S K (The Indian Journal of Agricultural Sciences, 2013)
In sorghum [(Sorghum bicolor (L.) Moench] numerous male sterile lines for grain sorghum are available. However, there is need of their critical evaluation for important fodder related traits. Therefore, the present study was undertaken to classify the variability available in these male sterile lines for such traits. Statistical analysis was carried out using the SPSS software. Correlation matrix was used to extract the principal components. Unweighted Pair-Group Method using Arithmetic Averages method of hierarchical cluster analysis was utilized with City Block distances to classify the male sterile lines. Significant amount of variability was observed for almost all the traits. Through principal factor analysis fourteen variables were reduced to five principal factors explaining 72.55 per cent variability. The first principal factor (PF) showed high loading for three disease resistance variables and PF 2 ascribed for fodder yield variables, i e plant height, green fodder yield/plant and dry fodder yield/plant. Hierarchical cluster analysis classified ninety one male sterile lines into ten clusters containing one to thirty five lines. The results of hierarchical cluster analysis and principal factor analysis confirmed the findings of each other. The male sterile lines like IMS 9A, 56A, 95A, AKMS 14A, 27A, ICSA 51, ICS 25A, 41251A, 41253A, etc., found to be superior using principal factor analysis were also found to be members of the best performing clusters, i e cluster II, VII and IX.